Work-Related Musculoskeletal Disorders Among Hospital Midwives in Chenzhou, Hunan Province, China and Associations with Job Stress and Working Conditions - Cao W; Hu L; He Y; Yang P; Li X; Cao S (Dove Medical Press, 2021)
Wenjing Cao,1 Lin Hu,2 Yongmei He,3 Ping Yang,4 Xiaoling Li,5 Shunwang Cao6 1Nursing School of Xiang Nan University, Chenzhou, Hunan, People's Republic of China; 2School of Public Health of Xiang Nan University, Chenzhou, Hunan, People's Republic of China; 3Department of Nursing, The Affiliated Hospital of Xiangnan University, Chenzhou, Hunan, People's Republic of China; 4Department of Gastroenterology, The Affiliated Hospital of Xiangnan University, Chenzhou, Hunan, People's Republic of China; 5Rehabilitation School of Xiang Nan University, Chenzhou, Hunan, People's Republic of China; 6Department of Laboratory Medicine, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People's Republic of ChinaCorrespondence: Shunwang CaoDepartment of Laboratory Medicine, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People's Republic of ChinaTel +86 15625053283Email cswang2010@163.comBackground: Midwives have a high risk of work-related musculoskeletal disorders (WMSDs), which are the leading cause of pain and disability. However, the association between job stress and WMSDs among midwives has not been studied. The aim of this project was to specifically describe relationships between the job stress and WMSDs among a sample of hospital midwives in Chenzhou, Hunan Province, China.Methods: We conducted a cross-sectional study among a sample of 769 eligible midwives in the city of Chenzhou in Hunan Province, China from May 2018 to January 2019. All participants completed a questionnaire regarding the presence and severity of different pain symptoms and job stress assessed by the Korean occupational stress scale.Results: A total of 597 participants responded (77.6%), and 491 (82.2%) reported that they had experienced WMSDs at some time over a 12-month period. The most common pain site was low back (72.7%), followed by the neck (52.8%) and shoulders (42.7%). We revealed that various aspects of job stress were associated with WMSDs in the current study, namely "Owing to my workload, I always feel time pressure" (OR, 2.05; 95% CI: 1.28- 3.28), "My job has become increasingly overbearing" (OR, 2.34; 95% CI: 1.46- 3.77), "My work requires long lasting concentration" (OR, 3.50; 95% CI: 2.13- 5.74), "I have to do various jobs simultaneously", (OR, 3.15; 95% CI: 1.93- 5.14)), "My work requires creativity" (OR, 2.15; 95% CI: 1.31- 3.54), "My work requires a high level of skill or knowledge" (OR, 2.83; 95% CI: 1.67- 4.80), "My supervisor is helpful in getting the job done" (OR, 0.53; 95% CI: 0.33- 0.84), "I have someone who understands my difficulties at work" (OR, 0.53; 95% CI: 0.34- 0.85), "Undesirable changes (ie, downsizing) will come to my job" (OR, 3.28; 95% CI: 2.01- 5.77), "My company provides me with sufficient organizational support" (OR, 0.47; 95% CI: 0.29- 0.74), "Departments cooperate each other without conflicts" (OR, 0.50; 95% CI: 0.32- 0.80), "I am provided with the opportunity to develop my capacity" (OR, 0.57; 95% CI: 0.36- 0.91) and "My company climate is authoritative and hierarchical" (OR: 3.21; 95% CI: 1.97-5.23).Conclusion: Overall, this study suggests that job stress has an important influence on WMSDs among a sample of hospital midwives in Chenzhou, Hunan Province, China. Given the multifaceted nature of identified risk, a comprehensive approach to reduce this risk is clearly required and a job stress management program will be essential.Keywords: midwife, work-related musculoskeletal disorders, job stress